2012
DOI: 10.4103/0973-1482.98978
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in Kashmir, India: Burden and pattern of disease

Abstract: Pattern of malignancies in valley is different from rest of the India. Gastrointestinal malignancies are the commonest malignancies in Kashmir valley followed by lung cancer in males and breast cancer in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 7 publications
2
25
1
1
Order By: Relevance
“…Gastric cancer is the third most common cancer in Kashmir only superseded by esophageal and lung cancer [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is the third most common cancer in Kashmir only superseded by esophageal and lung cancer [5]. …”
Section: Introductionmentioning
confidence: 99%
“…3 In a recent hospital based study in our Kashmir valley carcinoma of the ovary was observed to be the fourth most common cancer in females. 4 No age is exempted from developing ovarian tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is the most common cancer in Kashmir. [5][6][7] The annual age adjusted incidence rate for esophageal cancer in Kashmir is 43.6 and 27.9 per 10 5 persons in males and females, respectively. 6 Although several risk factors have been suggested, including hookah smoking and nass chewing, 8 oral hygiene, 9 animal contact, 10 low socioeconomic status, 11 major factors contributing to ESCC in Kashmir are yet to be established.…”
mentioning
confidence: 99%